2012
DOI: 10.1100/2012/434120
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Visual Neglect after Thrombolytic Treatment in Patients with Right Hemisphere Stroke

Abstract: Visual neglect (VN) is a common consequence of right hemisphere (RH) stroke. The aims of this study were to explore the presence of VN after RH stroke in the patients with (T+) or without (T−) thrombolytic treatment, and to determine whether thrombolysis is a predictor of VN. The study group consisted of 77 RH infarct patients. VN was evaluated with six conventional subtests of the Behavioural Inattention Test (BIT). Stroke severity was assessed using the National Institute of Health Stroke Scale (NIHSS). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Great strides had been made in the treatment of stroke, largely due to refined thrombolysis and new thrombectomy protocols. Patients who received thrombolytic treatment within 4.5 hours after ischemic stroke onset could expect a favourable 3-month clinical outcome, and it had been shown that thrombolysis could predict absence of neglect independently (Kettunen, Nurmi, Koivisto, Dastidar, & Jehkonen, 2012). When COVID-19 hit in early 2020 it was first thought to affect the respiratory system, but early clinical reports soon linked it to an increased risk of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Great strides had been made in the treatment of stroke, largely due to refined thrombolysis and new thrombectomy protocols. Patients who received thrombolytic treatment within 4.5 hours after ischemic stroke onset could expect a favourable 3-month clinical outcome, and it had been shown that thrombolysis could predict absence of neglect independently (Kettunen, Nurmi, Koivisto, Dastidar, & Jehkonen, 2012). When COVID-19 hit in early 2020 it was first thought to affect the respiratory system, but early clinical reports soon linked it to an increased risk of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients with right hemisphere stroke, Laihosalo et al (2011) found that patients treated with t-PA demonstrated significantly better visuoconstructional abilities compared to non-treated patients 4 days post-stroke. Treated patients also demonstrated an overall reduction in the presence of visual neglect and improved attentional processing (Kettunen et al 2012a(Kettunen et al , 2012b. Similarly, Jacquin et al (2014) found that the severity of aphasia was significantly milder in left hemisphere stroke patients treated with t-PA 1 week post-stroke; however, these differences did not persist when measured at 3 months.…”
Section: Discussionmentioning
confidence: 91%
“…Kettunen, Nurmi, Koivisto, Dastidar, and Jehkonen (2012) observed that thrombolysis was an independent predictor of the absence of neglect in right hemisphere stroke patients. According to literature, the study of Nys et al (2006) did not show any difference in cognitive performance when comparing patients who had received thrombolysis to those who did not.…”
Section: Discussionmentioning
confidence: 96%